Fiber Bragg grating and long period grating sensor for simultaneous measurement and discrimination of strain and temperature effects - Srimannarayana, Kamineni; Sai Shankar, Madhuvarasu; L.N. Sai Prasad, Ravinuthala; Krishna Mohan, T.K.; Ramakrishna, S.; Srikanth, G.; Ravi Prasad Rao, Sriramoju (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Fiber Bragg grating sensors are novel in the determination of various physical parameters. In the case of fiber Bragg grating, on a single measurement of wavelength shift, it is impossible to differentiate between the effects of changes in strain and temperature. The simulation of fiber Bragg grating, long period grating characteristics and use of the different strain-temperature response of combined sensor for the simultaneous measurement and discrimination of strain and temperature in C band are demonstrated.
Optica Applicata, Vol. 38, 2008, nr 3, s. 601-608
Keywords: optyka; fiber Bragg grating; long period grating; discrimination of strain and temperature